Physicochemical and Biological Indicators of Soils in an Organic Farming System - Beybit Nasiyev; Tursunay Vassilina; Ainur Zhylkybay; Vladimir Shibaikin; Akmarzhan Salykova (The Scientific World Journal)
In developed countries, the ideas of ecological agricultural production, continuous cycle, and waste-free production technologies have gained popularity. The effect from the production and consumption of ecological agricultural products is determined by the least harm to the environment, increasing the competitiveness of products, and receiving additional profit from increasing prices for higher quality products. The production of organically safe products is based on the principle of biologization, i.e., the widespread use of biological preparations, a high proportion of legumes (sources of nitrogen), and avoiding chemical plant protection products, transgenic plants, and genetically modified organisms (GMOs). This study aims to increase the productivity of safflower and improve the physicochemical and biological indicators of dark chestnut soils through the use of biologized technologies in the organic farming system. Standard methods for assessment and statistical analysis of physical and chemical parameters of soils were carried out in zone 1 of West Kazakhstan. This made it possible to identify the most optimal technology for the cultivation of safflower. The study results showed that under the influence of the phytomeliorative action of safflower in the 0–20 cm layer of dark chestnut soils, one could note an increase in the content of nitrate nitrogen by 5.95%, an increase in the content of mobile phosphorus by 5.22%, and soil loosening by 0.010 g/cm3, with the structure of the soil being 64.43%. Strong biological activity of the soil was established by the crops of safflower. The highest yield of safflower oil about 0.23 t/ha with an oil content of 30.1% was obtained using the biologized technology option. The use of biological technology, along with biological yields, increases oil yield by 0.06 t/ha or 28.06%.